Integration of Climate Change Education in Islamic Leadership Training Through Circular Economy Principles - Rahmania, Erfin Walida; Zainiyati, Husniyatus Salamah; Syafi’i, Imam; Fahmi, Muhammad; Dana Kusuma, Suteja Wira (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to describe how climate-change education is integrated into Islamic education through the principles of the Circular Economy and to analyse changes in students' understanding before and after the Islamic Leadership Training program. Conducted at Muhammadiyah 4 Surabaya Elementary School, this qualitative case study approach, supported by quantitative descriptive data, involved 24 sixth-grade students, the vice-principal, the teacher, and the committee member. The research team collected data through participatory observation, semi-structured interviews, documentation, and pre- and post-questionnaires. The analysis followed the Miles and Huberman interactive model, focusing on identifying patterns of Circular Economy integration within Islamic educational activities and mapping their influence on student learning. The results show that Circular Economy principles—reduce, reuse, recycle, repair, and rethink—were effectively implemented through Islamic Leadership Training programs such as worship routines, reflective discussions, and environmental practices. After Islamic Leadership Training, students demonstrated higher knowledge of 5R concepts, stronger environmental attitudes, and greater religious responsibility as khalifah fil ardh. The integration encourages behavioural change, reflective thinking, and a sense of social responsibility among students, aligning with the objectives of climate change education in fostering reasoning, socio-emotional awareness, and environmental action. The originality of this study lies in mapping the implementation of Circular Economy principles within religious education contexts, an area rarely explored in prior research. However, this study is limited to one Islamic elementary school, so the findings may not be generalised to other contexts. Future studies are recommended to expand the analysis to different educational settings to develop a replicable model for integrating Circular Economy-based climate education in Islamic schools.